Effectiveness of Punishment and Operating Subsidy in Supervision of China's Pension PPP Projects: An Evolutionary Game and Simulation Analysis. (28th November 2019) - Yue, Xianghua; Lin, Yuming
Abstract : Aiming at solving problems of service quality supervision in China's pension PPP projects, this paper mainly analyses the influences of "punishment" and "operating subsidy" on the evolutionary stability strategies of both players through constructing an evolutionary game model between private investors and government regulators. The results show that improving operating subsidy can effectively motivate private investors to improve service quality, and under the active supervision of government regulators, increasing punishment can restrain private investors from violating rules. If government regulators fail to perform their duties, however, punishment will be ineffective to private investors who have broken the rules. Therefore, the Chinese government should take appropriate measures to improve the sense of responsibility of government regulators who appropriately punish private investors providing low-quality services and appropriately increase operating subsidies to private investors offering high-quality services.